Dissipation and its consequences in the scaling exponents for a family of two-dimensional mappings - de Oliveira, Juliano A. [UNESP]; Leonel, Edson Denis [UNESP] (Iop Publishing Ltd, 2012)
The effects and consequences of dissipation in the scaling exponents describing the behaviour of average properties over the chaotic dynamics for a family of two-dimensional mappings are studied. The mapping is parametrized by an exponent gamma in one of the dynamical variables and by a parameter delta is an element of [0, 1], which denotes the amount of the dissipation. The Lyapunov exponents are obtained for different values of gamma and delta in the range 0 < delta < 1. The behaviour of the approaching orbits to the chaotic attractors is described analytically to be of exponential type. The deviation around the average action for chaotic orbits was described by a single set of scaling exponents obtained for different gamma leading the model to fall into the same universality class as that of the dissipative bouncer model.